2016
DOI: 10.1186/s12957-016-0984-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-582-5P induces colorectal cancer cell proliferation by targeting adenomatous polyposis coli

Abstract: BackgroundmicroRNA (miRNAs) dysregulation is widely involved in cancer progression and contributed to sustained cell proliferation by directly targeting multiple targets. Therefore, better understand the underlying mechanism of miRNA in carcinogenesis may improve diagnostic and therapeutic strategies for malignancy.MethodsWe assessed microRNA-582 (miR-582-5P) expression in colorectal cancer (CRC) specimens and cell lines by real-time PCR. Luciferase reporter assay was used to confirm the target associations. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Interestingly, several lines of evidence have reported that miR-582-3p and miR-582-5p simultaneously act as oncogene or tumor suppressor in different types of cancer. In colorectal cancer and non-functioning pituitary adenomas, miR-582-3p and miR-582-5p expression were simultaneously upregulated and function as oncogenic miRNA 37, 39, 41. Conversely, miR-582-3p and miR-582-5p expression have been reported to be strongly decreased in bladder cancer tissues, in which they played tumor-suppressive roles 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several lines of evidence have reported that miR-582-3p and miR-582-5p simultaneously act as oncogene or tumor suppressor in different types of cancer. In colorectal cancer and non-functioning pituitary adenomas, miR-582-3p and miR-582-5p expression were simultaneously upregulated and function as oncogenic miRNA 37, 39, 41. Conversely, miR-582-3p and miR-582-5p expression have been reported to be strongly decreased in bladder cancer tissues, in which they played tumor-suppressive roles 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Study by Maeno et al demonstrated that up-regulation of miR-582-5p facilitated cellular proliferation of prostate cancer cells under androgen-deprived conditions[11]. In colorectal cancer, miR-582-5p has showed to elevate cell growth rate by targeting adenomatous polyposis coli (APC)[26]. The exact function of miR-582-5p in NSCLC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate a variety of biological processes and they exert their functions under both physiological and pathological conditions, including cell proliferation, apoptosis, development and metabolism (22). To date, many studies have reported that miRNAs are associated with colon tumors.…”
Section: Discussionmentioning
confidence: 99%